2021
DOI: 10.48550/arxiv.2108.13298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

E-Commerce Promotions Personalization via Online Multiple-Choice Knapsack with Uplift Modeling

Abstract: Promotions and discounts are essential components of modern e-commerce platforms, where they are often used to incentivize customers towards purchase completion. Promotions also affect revenue and may incur a monetary loss that is often limited by a dedicated promotional budget. We study the Online Constrained Multiple-Choice Promotions Personalization Problem, where the optimization goal is to select for each customer which promotion to present in order to maximize purchase completions, while also complying w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Given the importance and unique challenges of uplift modeling, researchers in academia and industry have done extensive research in recent years. Uplift prediction models have evolved from metalearners-based [4,19,23], tree and forest-based [1,3,9,24,29,30], Knapsack problem-based [2,14] to deep neural networks-based architecture. Notably, many recent works have focused on developing new neural network architectures to better adapt to uplift modeling in industrial scenarios and shown remarkable performance improvements, such as EUEN [18], DESCN [34] and EFIN [21] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance and unique challenges of uplift modeling, researchers in academia and industry have done extensive research in recent years. Uplift prediction models have evolved from metalearners-based [4,19,23], tree and forest-based [1,3,9,24,29,30], Knapsack problem-based [2,14] to deep neural networks-based architecture. Notably, many recent works have focused on developing new neural network architectures to better adapt to uplift modeling in industrial scenarios and shown remarkable performance improvements, such as EUEN [18], DESCN [34] and EFIN [21] and so on.…”
Section: Introductionmentioning
confidence: 99%